Unwanted Pregnancy and Maternal Mental Health Based on the WHO SRQ-20: A Meta-Analysis - Muhamad Zakki Saefurrohim; Akhmad Azmiardi; Ratih Wirapuspita Wisnuwardani; Moch Thoriq Assegaf Al-Ayubi; Ray Wagiu Basrowi; Roma Yuliana (Masters Program in Public Health, 2025)
Background: The WHO (2019) reported that approximately 10% of pregnant women and 13% of postpartum women globally experience maternal mental health disorders. Several studies have identified unintended pregnancy as a contributing factor to these disorders. This systematic review and meta-analysis aimed to analyze and estimate the association between unintended pregnancy and maternal mental health disorders (MHD), using studies that applied the WHO Self-Reporting Questionnaire-20 (SRQ-20).Subjects and Method: A systematic review and meta-analysis followed PRISMA guidelines and was registered in PROSPERO (CRD42025634410). Article searches were conducted up to January 15, 2025, in PubMed, ScienceDirect, Google Scholar, and Scopus using the keywords: “SRQ” AND (“mental health” OR “psychological well-being” OR “mental disorder”) AND (“unwanted pregnancy” OR “unintended pregnancy” OR “unplanned pregnancy”) AND (“mother” OR “maternal”). Inclusion criteria focused on observational studies using the WHO SRQ-20 to assess maternal mental health among women with unintended and intended pregnancies. Meta-analysis was performed using R Studio, with effect sizes reported as risk ratios (RR) or adjusted odds ratios (aOR) and 95% confidence intervals. Heterogeneity was assessed using the I² statistic, and funnel plots were generated to examine publication bias.Results: A total of 12 studies from Ethiopia, Indonesia, India, Vietnam, Brazil, and Malawi, comprising 85,862 participants, were included in this meta-analysis. A total of 12 studies with a total of 85,862 participants were analyzed in this meta-analysis. The results showed that unintended pregnancy significantly increased the risk of maternal MHD. This finding was consistent in both cohort and cross-sectional studies, with effect sizes of (RR = 1.49; CI95%= 1.03 to 2.15; p= 0.030) and (aOR= 1.83; CI95%= 1.35 to 2.47; p < 0.001), respectively.Conclusion: These findings highlight the strong association between unintended pregnancy and MHD. Limitations include high heterogeneity among studies, potential publication bias, and the predominance of observational designs, which preclude causal inferences. Despite these limitations, the results underscore the need for interventions that prioritize the overall health of pregnant women.